(untitled) (Research, Society and Development, 2020)
This article presents the development and construction of a didactic kit of practical experiences of electrical circuits, remotely controllable through the internet, from low cost resources and devices, and easy to implement. Developed with open source technologies, the practice module was built from a Raspberry Pi, and subdivided into four parts: a web application (developed in Html, Css, Javascript, PHP and MySQL) and a local application coded in Python and runs on the Raspberry; two electronic boards, one for controlling the resistors of a circuit and the other as a variable power supply for the circuit; a cabinet designed and built in MDF to accommodate all the physical components of the equipment; and a mixed electrical circuit for experiments, consisting of 9 resistors, 10 voltmeters and 3 ammeters. To access remotely, a Login system was built, generating greater security and a button interface that, when triggered, make requests to a server, recording the status of the button pressed in an SQL Database (Structured Query Language). Tests were carried out to check the integrity of the hardware and software devices of the didactic kit, considering that they did not present any flaws, allowing the equipment to be installed in a physics laboratory, connected to the internet and made available intermittently for use by high school students.